2019
DOI: 10.3390/ijgi8080324
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Spatial Features of the E-RetailingEconomic Linkages at County Level: A Case Study for Zhejiang Province, China

Abstract: Quantitatively evaluating the spatial characteristics of regional e-retailing economy linkages is of great significance for clarifying the spatial organization of regional e-retailing economies, and promoting regional coordinated development. However, due to the lack of study data, it is difficult toconduct quantitative research on these regional e-retailing economic linkages. Taking advantage of emerging new data sources, the depth and breadth of related research cannow be improved. This paper considers 64 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Zhao et al (2017) used network analysis to show that the Pearl River Delta region was characterized by cross-regional interactions between market-oriented sectors [28]. Shen et al (2019) found significant east-west gradient differences between counties in Zhejiang [29], and Meng et al (2021) used gravity models to illustrate barycentric expansion of urbanization, industrialization, and carbon emissions in China [26]. Despite analytical differences, these findings show that UA involve integration and development across regional disparities and gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al (2017) used network analysis to show that the Pearl River Delta region was characterized by cross-regional interactions between market-oriented sectors [28]. Shen et al (2019) found significant east-west gradient differences between counties in Zhejiang [29], and Meng et al (2021) used gravity models to illustrate barycentric expansion of urbanization, industrialization, and carbon emissions in China [26]. Despite analytical differences, these findings show that UA involve integration and development across regional disparities and gradients.…”
Section: Introductionmentioning
confidence: 99%
“…Extra-firm relationships can be identified through product distribution relationships, such as service and consumption relationships [26][27][28]. Consumption relationships are especially enlightening for urban networks studies [29]. e government is often the largest consumer in a country [30], as it needs to purchase goods and services from domestic and foreign firms for government departments and affiliated groups to perform its daily state activities and offer services to the general public [31].…”
Section: Introductionmentioning
confidence: 99%